From autobiographical discourse to psychoanalytical discourse:: The relationship to the other in Malika Mokeddem - MESLOUH, Faouzia (Journal of Human Sciences, 2023)
This article proposes to analyze the relationship to the other in the writing of Malika Mokeddem. We show that the relationship to the other does not only manifest itself explicitly and consciously but also can be latent in the unconscious. In his self-writing, Mokeddem shows that the relationship to the other is first of all the relationship to man. Because even if the woman occupies the major role with her dominant “I”, the man is closely close to her. We demonstrate how the images of the other can manifest themselves implicitly, through the repressed memories in the unconscious of the Mokeddemian autobiographical discourse. For this we appeal to Freud’s work on literature. Thus, just like the dream, the Mokeddemian autobiographical discourse represents the fulfillment of a repressed desire, through which the relationship to the masculine other is manifested.